2020
DOI: 10.3390/cancers12040908
|View full text |Cite
|
Sign up to set email alerts
|

Karyopherin-β1 Regulates Radioresistance and Radiation-Increased Programmed Death-Ligand 1 Expression in Human Head and Neck Squamous Cell Carcinoma Cell Lines

Abstract: Nuclear transport receptors, such as karyopherin-β1 (KPNB1), play important roles in the nuclear-cytoplasmic transport of macromolecules. Recent evidence indicates the involvement of nuclear transport receptors in the progression of cancer, making these receptors promising targets for the treatment of cancer. Here, we investigated the anticancer effects of KPNB1 blockage or in combination with ionizing radiation on human head and neck squamous cell carcinoma (HNSCC). HNSCC cell line SAS and Ca9-22 cells were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…We next elucidated the functions of ACP-1n against cancer growth [13,35,39,40] and its functional significance in the maintenance of CRC in vitro by targeting BRD4 and BRD4driven gene expression in colorectal cancer HCT116 cells. Consistent with the previous results from an in vitro droplet formation assay (Figure 1C), immunofluorescent confocal imaging of BRD4 proteins demonstrated that the numbers of BRD4 puncta (representing BRD4 assembly) significantly decreased following ACP-1n treatment (Figure 2A,B).…”
Section: Aminocyclopropenone Compound Acp-1n Prevented Super-enhancer-driven Myc Expression By Blocking Brd4 Assembly In the Nucleusmentioning
confidence: 99%
“…We next elucidated the functions of ACP-1n against cancer growth [13,35,39,40] and its functional significance in the maintenance of CRC in vitro by targeting BRD4 and BRD4driven gene expression in colorectal cancer HCT116 cells. Consistent with the previous results from an in vitro droplet formation assay (Figure 1C), immunofluorescent confocal imaging of BRD4 proteins demonstrated that the numbers of BRD4 puncta (representing BRD4 assembly) significantly decreased following ACP-1n treatment (Figure 2A,B).…”
Section: Aminocyclopropenone Compound Acp-1n Prevented Super-enhancer-driven Myc Expression By Blocking Brd4 Assembly In the Nucleusmentioning
confidence: 99%
“…Hazawa et al. [ 37 ] demonstrated that importazole (an inhibitor of KPNB1 ) increased the expression level of p53‐upregulated modulator of apoptosis ( PUMA ) and decreased the expression level of nucleoporin 62 ( NUP62 ) by attenuating ΔNp63α nuclear import, which ultimately enhanced apoptosis in SCC cells. However, it was not clarified whether ΔNp63α ‐mediated nuclear transport is involved the regulation of ncRNAs in the OSCC process.…”
Section: Overview On Oscc and Chemoresistancementioning
confidence: 99%
“…We previously reported that KPNB1 inhibition increases cytotoxicity in various cancer cells, including HNSCC cells. It also increases radiosensitivity and enhances radiation-induced apoptosis specifically in HNSCC cells [ 10 ], suggesting that KPNB1 can transport nucleoproteins that specifically regulate radioresistance in HNSCC cells.…”
Section: Introductionmentioning
confidence: 99%